2018
DOI: 10.1016/j.ajic.2018.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Tweeting about measles during stages of an outbreak: A semantic network approach to the framing of an emerging infectious disease

Abstract: This study proposed and tested a method for assessing the frames used in social media discussions about EIDs based on the creation, interpretation, and quantification of semantic networks. Public health agencies could use social media outlets, such as Twitter, to assess how the public makes sense of an EID outbreak and to create adaptive messages in communicating with the public during different stages of the crisis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 17 publications
2
38
0
1
Order By: Relevance
“…These reports, or discussions surrounding the reports, were a focus of Twitter discourse. This is consistent with research that found people shared news updates, medical information, and scientific knowledge during a previous measles outbreak (Tang et al, 2018). Although the cluster is small, especially in comparison to the HPV/cancer prevention cluster, the MMR autism debate is still a topic of discussion on Twitter.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These reports, or discussions surrounding the reports, were a focus of Twitter discourse. This is consistent with research that found people shared news updates, medical information, and scientific knowledge during a previous measles outbreak (Tang et al, 2018). Although the cluster is small, especially in comparison to the HPV/cancer prevention cluster, the MMR autism debate is still a topic of discussion on Twitter.…”
Section: Discussionsupporting
confidence: 84%
“…Deriving from the cognitive paradigm and the linguistic theory of frame semantics (Fillmore, 1982), SNA can highlight the most salient information in a body of text by assessing the networks that emerge. Previous studies have used this approach with other socio-scientific subjects, such as the representation of the HPV vaccine online (Ruiz and Barnett, 2015), genetically engineered foods (Jiang et al, 2018), and Twitter posts during an emerging outbreak (Tang et al, 2018). A better understanding of the eco-system for childhood vaccine themes on social media can help vaccine promotion by targeting what information social media discourse lacks.…”
Section: Themes Of Vaccine Discourse On Social Mediamentioning
confidence: 99%
“…Past research indicates that the types of social media content can vary over the course of an outbreak and political framing of social media messages in past outbreaks appeared more frequently during the "maintenance" stage of outbreak response, which occurs during peak activity of response efforts prior to the resolution of an outbreak [39]. Ebola response activities within the US and the time period of interest in this study corresponded with the lead up to US midterm elections (which occurred Nov 4, 2014).…”
Section: Intersection Of Misinformation Political Content and Discordmentioning
confidence: 99%
“…For example, the study of Kim et al [20] identified core keywords and sub-topic groups of studies in domestic and geriatric frailty syndrome by analysing and clustering keywords based on the co-occurrence frequency and centrality analysis. The work of Thag et al [21] performed an unsupervised analysis to explore how the word frequencies and their co-occurrence can be applied for assessing the frames used in social media discussions. The authors focused their work in the emerging infectious diseases in the United States and based their study in the creation, interpretation, and quantification of semantic networks.…”
Section: Related Workmentioning
confidence: 99%